2007
DOI: 10.1007/s00439-007-0447-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel KCNQ4 pore-region mutation (p.G296S) causes deafness by impairing cell-surface channel expression

Abstract: Mutations in the potassium channel gene KCNQ4 underlie DFNA2, a subtype of autosomal dominant progressive, high-frequency hearing loss. Based on a phenotype-guided mutational screening we have identified a novel mutation c.886G>A, leading to the p.G296S substitution in the pore region of KCNQ4 channel. The possible impact of this mutation on total KCNQ4 protein expression, relative surface expression and channel function was investigated. When the G296S mutant was expressed in Xenopus oocytes, electrophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 43 publications
4
53
0
Order By: Relevance
“…In this report, we have confirmed impaired cell surface expression of the pore segment mutation G296S of hKv7.4 (18) and have demonstrated that all known pore region mutations of the channel that have been reported to cause progressive hearing loss in humans (L274H, W276S, L281S, and G285C) exhibit similar expression phenotype. Functionally, none of the pore segment mutants yielded measurable current.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In this report, we have confirmed impaired cell surface expression of the pore segment mutation G296S of hKv7.4 (18) and have demonstrated that all known pore region mutations of the channel that have been reported to cause progressive hearing loss in humans (L274H, W276S, L281S, and G285C) exhibit similar expression phenotype. Functionally, none of the pore segment mutants yielded measurable current.…”
Section: Discussionsupporting
confidence: 62%
“…The remaining two missense mutations are located at S3 and the C-terminal domains. Only two mutant forms, G285S and G296S, have been evaluated at the cellular level to determine the functional implications in heterologous expression system (2,18).…”
mentioning
confidence: 99%
“…1, A and G). Similar mutations in KCNQ4 are known to interfere with plasma membrane expression (7,33,34). Indeed, neuronal somata in the vestibular ganglion of Kcnq4 dn/dn mice (5), which express the trafficking-deficient G286S mutant (7), showed intense cytoplasmic KCNQ4 labeling (Fig.…”
Section: Kcnq4 and Kcnq5 Are Not Expressed In Adult Vestibular Hair Cmentioning
confidence: 81%
“…KCNQ4 is a known deafness gene that encodes a potassium channel expressed in the inner and outer ear, and the P-loop is involved in the formation of the tetrameric structure and function of KCNQ4 channels (Figures 2a and c). 11 The c.806_808delCCT mutation predicts the in-frame deletion of serine at position 269 (p.S269del) within the conserved N-terminal region of the P-loop of KCNQ4. Twelve other deaf relatives were also heterozygous for the p.S269del variant, which was absent in all unaffected relatives ( Figure 1).…”
Section: Candidate Gene Sequencingmentioning
confidence: 99%